2012
DOI: 10.1002/14651858.mr000024.pub3
|View full text |Cite
|
Sign up to set email alerts
|

New treatments compared to established treatments in randomized trials

Abstract: Background The proportion of proposed new treatments that are ’successful’ is of ethical, scientific, and public importance. We investigated how often new, experimental treatments evaluated in randomized controlled trials (RCTs) are superior to established treatments. Objectives Our main question was: “On average how often are new treatments more effective, equally effective or less effective than established treatments?” Additionally, we wanted to explain the observed results, i.e. whether the observed dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(68 citation statements)
references
References 56 publications
2
66
0
Order By: Relevance
“…In fact, this prior puts more probability in the tail area than the distribution of the estimated hazard ratios for new drugs versus controls from several sets of historical trials (Djulbegovic et al, 2012) shown in sizes, but also of sampling variation. For this reason priors developed on this basis have been criticized for depending on the sampling variation in historical trials (Senn, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, this prior puts more probability in the tail area than the distribution of the estimated hazard ratios for new drugs versus controls from several sets of historical trials (Djulbegovic et al, 2012) shown in sizes, but also of sampling variation. For this reason priors developed on this basis have been criticized for depending on the sampling variation in historical trials (Senn, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The recent Cochrane Review used data extracted for this project and combined them with the only three other similar cohorts. 96 …”
Section: Recommendations For Future Workmentioning
confidence: 99%
“…We have also recommended that the database be extended in relation to its inclusion of sufficient data on differences in results between new and old interventions, to enable it to remain part of the portfolio of cohorts of trials included in the ongoing Cochrane Review. 96 We recommend that the database be made available to other researchers, subject to similar confidentiality agreements that governed the present project (similar because the rules governing data access have changed since this project began). We also recommend that the database include aspects aimed at enabling the quality of its data to be improved by such use.…”
Section: Recommendations For the Future Metadata Databasementioning
confidence: 99%
See 2 more Smart Citations